Application of UPLCâMS/MS for separation and quantification of 3Î±-Hydroxy Tibolone and comparative bioavailability of two Tibolone formulations in healthy volunteers - Vijay P. Shinde; Ashutosh Pudage; Arvind Jangid; Hiren Mistri; P.K. Patel (Elsevier, 2013)
A novel, fast, sensitive and robust method based on ultra-performance liquid chromatography coupled to atmospheric pressure electrospray ionization tandem mass spectrometry (UPLCâESI-MS/MS) has been developed to separate two Tibolone stereoisomers i.e., 3Î±-Hydroxy Tibolone and 3Î²-Hydroxy Tibolone and to quantify 3Î±-Hydroxy Tibolone using p-toulenesulfonyl isocyanate (PTSI) as a derivatizing reagent in human plasma. 3Î±-Hydroxy Tibolone-13CD3 was used as an internal standard (IS). The analyte and IS were extracted from human plasma by liquidâliquid extraction using ethyl acetate. Extracted samples were analyzed by UPLCâESI-MS/MS. Chromatography was performed using binary gradient on UPLC analytical column. A linear calibration curve over the range of 0.100â35.000Â ng/mL was obtained and lower limit of quantification (LLOQ) was 0.100Â ng/mL demonstrating acceptable accuracy and precision. This method was successfully applied to a pharmacokinetic study in order to compare a test Tibolone 2.5Â mg formulation vs. a reference 2.5Â mg Tibolone tablet formulation in 50 post-menopausal/surgical menopause female human volunteers under fasting conditions. It is concluded that test formulation of Tibolone is bioequivalent to reference formulation of Tibolone. Keywords: UPLC, Tibolone, Pharmacokinetics, p-toulenesulfonyl isocyanate